Liana - host tree associations in a subtropical montane forest of northwestern Argentina - Malizia, Agustina (2006)
In a subtropical montane forest of north-western Argentina (27°S, 1000 m elevation), we analysed the effect of crown illumination, trunk diameter, foliar phenology and tree species identity as determinants of liana–host tree associations, as well as the spatial pattern of liana abundance in a 6-ha permanent plot. We recorded 2346 liana individuals 2 cm and 2320 trees 10 cm dbh. Sixty-five per cent of the trees hosted at least one liana stem. Large and well-lit trees were more likely to support lianas and supported more liana abundance than small and shaded trees. Yet, when trees were standardized by their size (liana basal area/tree basal area ratio), lianas were more abundant in smaller and less-exposed trees. Foliar phenology and tree species identity showed no association with the frequency of liana colonization and their abundance. Overall, tree features played a minor or even neutral role in structuring the liana community within this forest. Instead, lianas showed a positive autocorrelation at spatial scales up to 40 m. This suggests that lianas might be mostly structured by light-and dispersal-related factors such as those involving canopy access or canopy disturbances, with a negligible effect of host species identity and foliar phenology.